A Faktor Risiko Kejadian Infeksi pada Bayi Baru Lahir dengan Sectio Caesarea di RSUD H. Abdul Aziz Marabahan - Feni Norlita Sari (Midwifery Departement Poltekkes Kemenkes Banjarmasin, 2025)
Abstract Newborn infections are a major cause of neonatal morbidity and mortality. Infants born via sectio caesarea (SC) are at higher risk of infection. Risk factors include premature rupture of membranes, low birth weight, and hyperbilirubin. In RSUD H. Abdul Aziz Marabahan in 2024 there were 492 SC cases with 291 cases of infection (59.1%). This study aims to analyze the risk factors for infection in newborns with SC. The study used an analytic descriptive design with a cross-sectional approach. The population in this study were all newborns with SC in 2024. The sample was 492 people in 2024. The variables studied included infection, KPD, LBW, and hyperbilirubin. Data analysis used chi-square test. Of 492 SC babies, 291 had infection (59.1%). There were 43 cases of KPD (8.7%), 63 LBW (12.8%), and 35 hyperbilirubin (7.1%). There was a significant relationship between CKD and infection (p=0.000), there was a relationship between hyperbilirubin and infection (p=0.002) while LBW had no significant relationship with infection (p=0.580). Based on the results of the study, it can be concluded that there is a significant relationship between KPD and the incidence of infection, and there is a relationship between hyperbilirubin and the incidence of infection in SC babies, while LBW has no significant relationship with the incidence of infection. Prevention and early detection of risk factors need to be done to reduce neonatal infection rates. Keyword: Infection, Newborn, Cesarean Section